Study on Thermal Performance of Closed-loop Heat Pump Drying System - Meng Zhaofeng; Zhang Fan; Liu Yin; Cui Xiangna; Hu Rusheng; Wang Shun; Du Chenyang (Zhileng xuebao)
This study analyzed the effects of compressor speed, expansion valve opening, and drying temperature on the thermal performance of a closed-loop heat pump drying system through single-factor experiments. Subsequently, system performance variation characteristics were obtained. The results show that when the compressor speed was increased from 2 000 r/min to 3 000 r/min, the power consumption increased by 89.6%, the heating capacity increased by 11.4%, and the COP（coefficient of performance） decreased by 41.3%. When the expansion valve was opened from 30% to 80%, the power consumption decreased by 5.2%, heating capacity increased by 73.5%, and COP decreased by 82.9%. When the drying temperature was increased from 40 °C to 60 °C, the power consumption increased by 38.1%, the heating capacity increased by 3.1%, and the COP decreased by 25.3%. Based on the analysis of the research results, it can be concluded that increasing the opening of the expansion valve and reducing the drying temperature and compressor speed can effectively reduce the system power consumption and improve the system performance.